Curcumin played an anti-cancer role in colorectal cancer via mediating circ_KIAA1199-related regulatory axis - SUN,Xue-Feng (2022)
Abstract Curcumin has been found to have anti-cancer role in many cancer, including colorectal cancer (CRC). However, it is not clear whether curcumin can be involved in CRC progression by mediating the circRNA regulatory axis. Curcumin inhibited the proliferation, migration, invasion, and promoted the apoptosis of CRC cells. Circ_KIAA1199 was an upregulated circRNA in CRC, and its overexpression could reverse the negative regulation of curcumin on CRC progression. MiR-433-3p was found to be sponged by circ_KIAA1199, and its mimic abolished the regulation of circ_KIAA1199 overexpression on the progression of curcumin-treated CRC cells. ADAM10 was a target of miR-433-3p and its expression was regulated by circ_KIAA1199 and curcumin. The suppressive effect of miR-433-3p inhibitor on the progression of curcumin-treated CRC cells could be reversed by ADAM10 silencing. Also, curcumin reduced CRC tumor growth by regulating the circ_KIAA1199/miR-433-3p/ADAM10 axis in vivo. Our data showed that curcumin could restrain CRC progression, which was achieved through the circ_KIAA1199/miR-433-3p/ADAM10 pathway.